Strategies for treatment of dystonia - Dressler, Dirk; Altenmueller, Eckart; Bhidayasiri, Roongroj; Bohlega, Saeed; Chana, Pedro; Chung, Tae Mo; Frucht, Steven; Garcia-Ruiz, Pedro J; Kaelin, Alain; Kaji, Ryuji; Kanovsky, Petr; Laskawi, Rainer; et al. (Journal of neural transmission (Vienna, Austria, 2016)
Treatment of dystonias is generally symptomatic. To produce sufficient therapy effects, therefore, frequently a multimodal and interdisciplinary therapeutic approach becomes necessary, combining botulinum toxin therapy, deep brain stimulation, oral antidystonic drugs, adjuvant drugs and rehabilitation therapy including physiotherapy, occupational therapy, re-training, speech therapy, psychotherapy and sociotherapy. This review presents the recommendations of the IAB-Interdisciplinary Working Group for Movement Disorders Special Task Force on Interdisciplinary Treatment of Dystonia. It reviews the different therapeutic modalities and outlines a strategy to adapt them to the dystonia localisation and severity of the individual patient. Hints to emerging and future therapies will be given.
Keywords: Deep brain stimulation; Interdisciplinary approach; Multimodal therapies; Humans; Treatment strategies; Dystonic Disorders; lidé; dystonické poruchy; Botulinum toxin; Rehabilitation therapy; Antidystonic drugs; Dystonia